PENGARUH SELF-CONCEPT DAN SELF-EFFICACY TERHADAP MOTIVASI BERPRESTASI MAHASISWA JURUSAN MANAJEMEN BERBASIS KKNI - AYN Warsiki; Tri Mardiana (Universitas Pembangunan Nasional Veteran Yogyakarta, 2019)
This study aims to determine 1) the effect of Self Concept on Achievement Motivation, 2) the effect of Self-Efficacy on Achievement Motivation 3) the joint influence of Self Concept and Self-Efficacy on Achievement Motivation. The subjects of this study were students majoring in management of FEB UPN